2014
DOI: 10.1002/2013jd020825
|View full text |Cite
|
Sign up to set email alerts
|

WACCM climate chemistry sensitivity to sprite perturbations

Abstract: Transient luminous events affect Earth's atmosphere between thunderstorm tops and the lower ionosphere through ion-neutral chemistry reactions. Particular emphasis has been given to sprites, with models and observations suggesting a capability of perturbing atmospheric nitrogen oxides at a local level, as it is known to occur for tropospheric lightning and laboratory air discharges. However, it is as yet unknown whether sprites can be a relevant source of nitrogen oxides for the upper atmosphere. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 72 publications
2
32
0
Order By: Relevance
“…According to previous local models of halos and elves (Pérez-Invernón, , their global chemical impact would be negligible. Arnone et al (2014) and Arnone and Dinelli (2016) estimated the global production of NO x by sprites using the Whole Atmosphere Community Climate Model version 4 (WACCM4). Arnone et al (2014) and Arnone and Dinelli (2016) found that a perturbation in the tropical concentration of nitrogen oxide by sprites could lie between 0.015 and 0.15 ppbv.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous local models of halos and elves (Pérez-Invernón, , their global chemical impact would be negligible. Arnone et al (2014) and Arnone and Dinelli (2016) estimated the global production of NO x by sprites using the Whole Atmosphere Community Climate Model version 4 (WACCM4). Arnone et al (2014) and Arnone and Dinelli (2016) found that a perturbation in the tropical concentration of nitrogen oxide by sprites could lie between 0.015 and 0.15 ppbv.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we will investigate the possibility to include NO x vibrational levels. Indeed, several authors have highlighted the potential production of NO x caused by sprites (Arnone et al, 2014;Enell et al, 2008;Gordillo-Vázquez, 2008;Hiraki et al, 2008;Nijdam et al, 2010;Peterson et al, 2009;Rodger et al, 2008;Sentman et al, 2008), but, to our knowledge, their vibrational kinetics have never been studied under sprite conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring atmospheric composition produced by single sudden sprite events has proven very difficult so far, although advanced heterodyne radio technologies have enabled the detection of minor species, such as active radicals in the upper atmosphere, by space submillimeter wave sounders (e.g., Kikuchi et al, 2010;Siegel, 2007;Waters et al, 2006;Yamada et al, 2018, and others) Sprites are one of the most familiar types of the various upper atmospheric lightning phenomena, which are characterized as transient luminous events (Neubert et al, 2008;Pasko et al, 2012). Since the discovery of the sprite in 1990 (Franz et al, 1990), it has been suggested that transient luminous events, particularly sprites, generate active radicals and ions by ion-neutral chemistry models (e.g., Arnone et al, 2014, Evtushenko et al, 2013, Gordillo-Vázquez, 2008, Parra-Rojas et al, 2015, Winkler & Notholt, 2014, although no conclusive observational evidence of chemical impact has been reported so far. Sprite discharges are induced by conventional air breakdown, caused by lightning-driven electric fields above thunderstorms (Hu et al, 2007;Pasko et al, 1995).…”
Section: Citationmentioning
confidence: 99%
“…The diurnal variation in mesospheric HO 2 is mostly controlled by the photolysis of H 2 O by sunlight , which only depends on the local time and lifetime of HO x species, making it incapable of producing the local enhancement. Horizontal transportation by zonal winds may impact the estimated HO 2 productions as demonstrated in Arnone et al (2014) for nitrogen oxides. The zonal winds are between 0 and 40 m/s at November (Events A and B) and between −20 and 0 m/s on March (Event C) near 75-to 80-km altitudes .…”
Section: 1029/2019gl085529mentioning
confidence: 99%
See 1 more Smart Citation